2005
DOI: 10.2174/1381612054546923
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Assisted Laser Desorption/Ionization Analysis of Non-Covalent Complexes: Fundamentals and Applications

Abstract: Mass spectrometry is now a well established and powerful method for analysing the structure of biomolecules and more recently their non-covalent interactions. It is based on two soft ionization techniques, electrospray ionization (ESI) and matrix-assisted laser desorption/ionization (MALDI), which allow to produce biomolecule ions in gas phase with a very high efficiency for a subsequent analysis in the mass analyser. The high sensitivity and the high precision of modern mass spectrometry were first applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 131 publications
(286 reference statements)
1
48
0
Order By: Relevance
“…The later approach, which uses aqueous solution at physiological pH, more specifically aqueous solution of sinapinic acid with ammonium citrate adjusted to pH 7 with ammonium hydroxide, is very effective for the study of noncovalent protein-protein interactions by MALDI as subsequently shown. This sample preparation method gives very homogeneous analyte distribution, and the simple "dried-droplet" was used and found to be sufficient to produce spectra of complexes [3]. The results for three protein complexes are summarized here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The later approach, which uses aqueous solution at physiological pH, more specifically aqueous solution of sinapinic acid with ammonium citrate adjusted to pH 7 with ammonium hydroxide, is very effective for the study of noncovalent protein-protein interactions by MALDI as subsequently shown. This sample preparation method gives very homogeneous analyte distribution, and the simple "dried-droplet" was used and found to be sufficient to produce spectra of complexes [3]. The results for three protein complexes are summarized here.…”
Section: Resultsmentioning
confidence: 99%
“…The laser desorption process itself may also dissociate some of the noncovalent complexes. Nevertheless, noncovalent complexes have been studied by MALDI with some success [3,4].…”
mentioning
confidence: 99%
“…Formation of aggregates in the gas-phase during MALDI process is a well-known phenomenon [28]. So, when studying noncovalent complexes between DNA and polybasic compounds, great care must be taken to be sure that observed complexes pre-exist in solution and are not formed in the gas phase.…”
Section: Control Experimentsmentioning
confidence: 99%
“…Another problem, shared with the ESI technique, is the possible formation in the gas phase of aggregates that do not reflect the in-solution species (leading to false positives). However, several works have shown that great care taken in sample preparation allowed the transfer of intact complexes from the solution to the gas phase via matrix crystals [12].…”
mentioning
confidence: 99%
“…Since the introduction of soft ionization methods, MS has become a valuable technique for characterizing noncovalent complexes. Usually, electrospray ionization (ESI) [15] or nanoelectrospray (nanoESI) mass spectrometry is preferred over matrix-assisted laser desorption/ionization mass spectrometry (MALDI MS) [16,17] for studying noncovalent complexes, such as protein-protein, proteinligand, protein-DNA, or DNA-DNA complexes. This is mainly because ESI is able to spray "native-like" aqueous solutions [18,19].…”
mentioning
confidence: 99%